2005
DOI: 10.1139/b05-022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the early stages of Colletotrichum acutatum infection of strawberry tissues

Abstract: Abstract:The early stages of the infection of attached leaves and petioles of strawberry (Fragaria ×ananassa Duch. 'Camarosa') by Colletotrichum acutatum Simmonds were studied using scanning and transmission electron microscopy. Pre-penetration events of these tissues were similar, but the production of secondary conidia (microcyclic conidiation) was detected only on leaves. At the ultrastructural level, different stages of maturation of appressoria were observed and described. In young appressoria, the cell w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
3
22
1
Order By: Relevance
“…This structure is an extension of the penetration peg wall and may act on the hydrostatic pressure at the penetration spot. However, in this study the appressorial cone was not observed, which is also the case of C. sublineolum (WHARTON et al, 2001), C truncatum (O'CONNELL et al, 1993) and C. acutatum (ARROYO et al, 2005). The lack of a cone in some species and its presence in others suggests that mechanism of infection by species of Colletotrichum depends on the host species.…”
Section: Suspensions Of 10contrasting
confidence: 68%
See 3 more Smart Citations
“…This structure is an extension of the penetration peg wall and may act on the hydrostatic pressure at the penetration spot. However, in this study the appressorial cone was not observed, which is also the case of C. sublineolum (WHARTON et al, 2001), C truncatum (O'CONNELL et al, 1993) and C. acutatum (ARROYO et al, 2005). The lack of a cone in some species and its presence in others suggests that mechanism of infection by species of Colletotrichum depends on the host species.…”
Section: Suspensions Of 10contrasting
confidence: 68%
“…The area of contact between the appressoria and the fruit surface was relatively narrow (Figure 1 I-K). After the formation of the penetration peg, the cuticle structure remained intact in the region near the pore, supporting the hypothesis that penetration occurs mainly through mechanical force, as reported for C. acutatum in strawberry (ARROYO et al, 2005). However, other factors, such as enzyme activation during the process need to be considered (O'CONNELL et al, 1985;KÖLLER, 1991).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The employment of both intracellular and subcuticular intramural infection strategies was reported in C. acutatum , C. gloeosporioides , and C. truncatum (Perfect et al , ; De Silva et al , ). Of these, only C. acutatum was observed to form subcuticular intramural infection vesicles in strawberry leaf tissues (Arroyo et al , ).…”
Section: Discussionmentioning
confidence: 99%